Ichthyosiform large plaque parapsoriasis: Report of a rare entity - Falguni Nag; Arghyaprasun Ghosh; Projna Biswas; Gobinda Chatterjee; Saugato Biswas (Wolters Kluwer Medknow Publications, 2013)
Large plaque parapsoriasis (LPP) is an idiopathic, chronic scaly dermatosis classified within parapsoriasis group of diseases, occurring commonly in middle aged patients of all races and geographic regions. LPP and its variants are closely related to the patch stage of mycosis fungoides. The two types of LPP mostly described are the poikilodermatous and retiform parapsoriasis. We are reporting an ichthyosiform LPP for its rarity.